Abnormal neural differentiation in response to graphene quantum dots through histone modification interference. (December 2022) - Ku, Tingting; Ren, Zhihua; Yang, Renjun; Liu, Qian S.; Sang, Nan; Faiola, Francesco; Zhou, Qunfang; Jiang, Guibin
Graphical abstract: Highlights: OH-GQDs inhibited the ectoderm development of the mESCs. Exposure to OH-GQDs reduced the neural precursor formation and neurogenesis. OH-GQDs selectively affected BMP pathway by disturbing histone modification. OH-GQDs elicited higher hazards on neurodevelopment than did NH2 -GQDs. Abstract: Graphene quantum dots (GQDs) have been broadly applied in biomedicine in recent years, and their environmental exposure and toxicological impacts have raised increasing concerns. The nanosafety assessment on the nervous system is one of the most important aspects, and potential effects of GQDs on neurodevelopment and the underlying mechanism are still elusive. In this study, the neural developmental toxicities of OH-GQDs and NH2 -GQDs were investigated using the mouse embryonic stem cells (mESCs). The results revealed that OH-GQDs significantly inhibited the ectoderm development, and reduced the neural precursor formation and neurogenesis during the neural differentiation of the mESCs. The exploration on the mechanism uncovered that the increased enrichment of H3K27me3 at the promoter region of the Smad6 gene was involved in histone modification-activated BMP signal pathway, which consequently influenced its regulatory effects on neural differentiation. Additionally, OH-GQDs elicited a stronger effect on inducing the imbalance of histone modification, and resulted in higher latency of neural differentiation disturbance than did NH2 -GQDs, suggesting surface functionalization-specific effects of GQDs on neurodevelopmental toxicity. This study would provide new insights in not only the adverse effects of GQDs on neurodevelopment, but also the influence from the chemical modification of GQDs on their bioactivities.